Salt intake and prevalence of overweight/obesity in Japan, China, the United Kingdom, and the United States: the INTERMAP Study. Issue 1 (21st May 2019) - Zhou, Long; Stamler, Jeremiah; Chan, Queenie; Van Horn, Linda; Daviglus, Martha L; Dyer, Alan R; Miura, Katsuyuki; Okuda, Nagako; Wu, Yangfeng; Ueshima, Hirotsugu; Elliott, Paul; Zhao, Liancheng; et al.
ABSTRACT: Background: Several studies have reported that dietary salt intake may be an independent risk factor for overweight/obesity, but results from previous studies are controversial, reflecting study limitations such as use of a single spot urine or dietary recall to estimate daily salt intake rather than 24-h urine collections, and population samples from only a single country or center. Objective: The aim of this study was to use data from the International Study of Macro-/Micro-nutrients and Blood Pressure (INTERMAP Study) to explore the relation between dietary salt intake estimated from 2 timed 24-h urine collections and body mass index (BMI; in kg/m 2 ) as well as prevalence of overweight/obesity in Japan, China, the United Kingdom, and the United States. Methods: Data were from a cross-sectional study of 4680 men and women aged 40–59 y in Japan ( n  = 1145), China ( n  = 839), the United Kingdom ( n  = 501), and the United States ( n  = 2195). General linear models were used to obtain the regression coefficients (β) of salt intake associated with BMI. Multivariable logistic regression models were used to determine the ORs and 95% CIs of overweight/obesity associated with a 1-g/d higher dietary salt intake. Results: After adjustment for potential confounding factors including energy intake, salt intake 1 g/d higher was associated with BMI higher by 0.28 in Japan, 0.10 in China, 0.42 in the United Kingdom, and 0.52 in the United States, all P values < 0.001. Salt intake 1 g/d higher was associated with odds of overweight/obesity 21% higher in Japan, 4% higher in China, 29% higher in the United Kingdom, and 24% higher in the United States, all P values < 0.05. Conclusions: Salt intake is positively associated with BMI and the prevalence of overweight/obesity in Japan, China, the United Kingdom, and the United States. This association needs to be further confirmed in well-designed prospective studies with repeated dietary and BMI measurements.This trial was registered at clinicaltrials.gov as NCT00005271.